Progress of high performance Ti3C2Tx MXene nanocomposite films for electromagnetic interference shielding. Issue 12 (8th March 2023) - Hu, Guirong; Cen, Zhuoqi; Xiong, Yuzhu; Liang, Kun
Abstract : Progress of MXene nanocomposite films with different layer structures of light weight, high flexibility, high mechanical strength, good hydrophobicity, and multifunctionality for EMI shielding. Abstract : With the rapid growth of 5G communication technology, it is imperative to produce electromagnetic interference (EMI) shielding materials to combat the growing electromagnetic radiation pollution. For new shielding applications, EMI shielding materials with high flexibility, light weight and good mechanical strength are in high demand. Due to their light weight, high flexibility, excellent EMI shielding performance, high mechanical properties, and multifunctionality, Ti3 C2 T x MXene nanocomposite films have shown absolute benefits in EMI shielding in recent years. Consequently, numerous lightweight and flexible high-performance Ti3 C2 T x MXene nanocomposite films have been generated quickly. In this article, we discuss not only the present state of EMI shielding material research, but also the synthesis and electromagnetic properties of Ti3 C2 T x MXene. In addition, the loss mechanism of EMI shielding is described, with an emphasis on the analysis and summary of the research progress of diverse layer structured Ti3 C2 T x MXene nanocomposite films for EMI shielding. Finally, the current issues of design and fabrication for Ti3 C2 T x MXene nanocomposite films that need to be addressed are proposed, as well as the future research direction for Ti3 C2 T x MXene nanocomposite films.